New house defects smart checklist based on QLASSIC standard - Nabilah, Mohd Yamin (2019)
House is a building that serves as living quarters for one or a family according to Merriam Webster which means everyone especially family needs a house to be lived in. A house is very important to a family institution, a good quality house to be exact. This issue is not only in Malaysia, but it is worldwide issue according to United Nation. Good quality house is definitely expensive, and some people cannot afford the house. Yes, there are some affordable houses, but the quality is poor and not meet the standard. Then, CIDB came out with solution which is QLASSIC. QLASSIC is a national standard for construction industry. QLASSIC is a short form of Quality Assessment System in Construction. QLASSIC is for both developer and public which is house buyer. Currently, CIDB only provides online quality guide book for homeowners which is home owner can download it on CIDB website. The quality checklist is provided in the online book and if there are some defects, home owner has to make a manual report. A manual report including writing a formal letter and send it to the developer’s office. Hence, there is no online tools for home owner and there is no analytical tools supporting systemic decision making for home owner. As a result, I would like to make a research on online online assessment for home owner. The smart checklist will contain seven attributes, and, in each attribute, there will be several conditions for that attributes. Each condition has one mark by default. So, the given mark will then be divided to total mark of the attribute. Hence, those mark will be stored in the database. The prototype will be developed using Limesurvey functionalities that had been modified with html coding and a simple database for storing data. Then, I will use Microsoft Excel to analyze the data and make a data visualization from it. Not to mention, these online checklists is an online report from home owner to developer, House Association etc. Finally, expected result will also benefit to House Association or maybe CIDB as the potential analytics that will come out from these data are major defects based on project, and the best part is the pattern of defects over time based on project, developer and region. With these analytics, prediction and prevention for next project can be made. Hence, will save lots of cost and time for developer or for related party.